The Bone Mineral Density Values in Fibromiyalgia Syndrome: A Risk Factor For Osteoporosis - Akın Erdal; Kadir Yıldırım; Hatice Hacıbeyoğlu; Mustafa Yıldırım; Kazım Şenel (Türk Osteoporoz Dergisi, 2003)
Fibromyalgia syndrome(FMS) is a chronic musculoskeletal disease characterized by widespread pain, tender points and clinical findings like, fatigue, sleep disturbances, irritable bowel syndrome. Because of the association with depression and sedantary life style, osteoporosis may be a problem in patients with fibromyalgia. This study was carried out to determine whether fibromyalgia is a risk factor in osteoporosis or not. Thirty-eight women with ages ranging from 25 to 50, meeting the American College of Rheumatology criteria for fibromyalgia and 20 healthy controls were included in the study. Lumbar spine and left femoral bone mineral density (BMD) values were determined with Hologic 2000 DEXA. Beck Depression Scale was used to determine the depression levels. BMD values were significantly lower in FMS group than controls in both lumbar and hip regions (p<0.05). There was also a negative significant correlation between Beck Depression Scale and BMD values in in both lumbar and hip regions (r = -0.537, p=0.001; r = -0.473, p=0.003, respectively). We concluded that fibromyalgia may be a risk factor for osteoporosis and the association with depression may have important implications. Early implementation of appropriate nutritional supplementation (calcium/vitamin D), and exercise and pharmacological therapy may be indicated in patients with FMS. Of Clearly further studies are needed on this subject.